A Mixed Protonic–Electronic Conductor Base on the Host–Guest Architecture of 2D Metal–Organic Layers and Inorganic Layers - He, Xing‐Lu; Shao, Bing; Huang, Rui‐Kang; Dong, Min; Tong, Yu‐Qing; Luo, Yan; Meng, Ting; Yang, Fu‐Jie; Zhang, Zhong; Huang, Jin (Advanced science, 2023)
The key to designing and fabricating highly efficient mixed protonic–electronic conductors materials (MPECs) is to integrate the mixed conductive active sites into a single structure, to break through the shortcomings of traditional physical blending. Herein, based on the host–guest interaction, an MPEC is consisted of 2D metal–organic layers and hydrogen‐bonded inorganic layers by the assembly methods of layered intercalation. Noticeably, the 2D intercalated materials (≈1.3 nm) exhibit the proton conductivity and electron conductivity, which are 2.02 × 10−5 and 3.84 × 10−4 S cm−1 at 100 °C and 99% relative humidity, much higher than these of pure 2D metal–organic layers (>>1.0 × 10−10 and 2.01×10−8 S cm−1), respectively. Furthermore, combining accurate structural information and theoretical calculations reveals that the inserted hydrogen‐bonded inorganic layers provide the proton source and a networks of hydrogen−bonds leading to efficient proton transport, meanwhile reducing the bandgap of hybrid architecture and increasing the band electron delocalization of the metal–organic layer to greatly elevate the electron transport of intrinsic 2D metal–organic frameworks. The guest particles of inorganic ions and/or molecules insert into the interlamination of neutral host framework 2D MOFs, manufacturing the host–guest architecture of 2D metal–organic layers and hydrogen‐bonded inorganic layers. The intercalated layer provides the proton source and reduces the bandgap of hybrid architecture, which leads to the high‐efficiency mixed protonic–electronic transport.